2013
DOI: 10.1016/j.ejmech.2013.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of phosphorodiamidate prodrugs of antiviral and anticancer nucleosides

Abstract: We herein report the application of the phosphorodiamidate phosphate prodrug approach to a series of thirteen nucleoside analogs with antiviral or anticancer activity. Twenty-five symmetrical phosphorodiamidates were synthesized, bearing esterified l-Alanine (and in one case d-alanine) in the prodrug moiety, each as single stereoisomer. The presence of an achiral phosphorus represents a potential advantage over the phosphoramidate ProTide approach, where diastereoisomeric mixtures are routinely obtained, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…Recently, McGuigan and colleagues have claimed just such advantages for a diamidate strategy [119,120]. When the amide is derived from an amino acid, achieving a neutral species requires esterification of the carboxyl group as well (e.g.…”
Section: Amidate Prodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, McGuigan and colleagues have claimed just such advantages for a diamidate strategy [119,120]. When the amide is derived from an amino acid, achieving a neutral species requires esterification of the carboxyl group as well (e.g.…”
Section: Amidate Prodrugsmentioning
confidence: 99%
“…60 ). After examination of a series of twenty-five diamidates for activity against HCV [120] and HIV replication, and anti-proliferative effects in several cell lines, it was found that this strategy is sufficient to afford good cellular activity with several different nucleoside analogues [119]. Furthermore, preparation of symmetrical bisamidates from the symmetrical diesters has been reported [121].…”
Section: Amidate Prodrugsmentioning
confidence: 99%
“…The SATE derivative of AZT, bis(tBuSATE)AZT-MP (Scheme 1), showed marked antiviral activity in thymidine kinase-deficient CEM cells in which AZT was virtually inactive, reaffirming the hypothesis that it exerts its activity via intracellular delivery of AZT 5′-monophosphate (Lefebvre et al, 1995). Phosphoramidates and phosphorodiamidates have been also explored as pronucleotides with improved bioavailability (McGuigan et al, 2013;Mehellou et al, 2009).…”
Section: Introductionmentioning
confidence: 82%
“…Other phosphate and phosphonate derivatives have been also developed (McGuigan et al, 2013); for example, S-acyl-2-thioethyl (SATE) groups are hydrolysed inside cells into the phosphodiester derivative by a nonspecific esterase, which subsequently liberates the nucleoside monophosphate by the action of a phosphodiesterase (Peyrottes et al, 2004). The SATE derivative of AZT, bis(tBuSATE)AZT-MP (Scheme 1), showed marked antiviral activity in thymidine kinase-deficient CEM cells in which AZT was virtually inactive, reaffirming the hypothesis that it exerts its activity via intracellular delivery of AZT 5′-monophosphate (Lefebvre et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although less extensively investigated than the ProTide approach, a second phosphoramidate strategy that has been reported by our group as a promising way to deliver nucleoside monophosphates into a cell, is the use of phosphorodiamidates . In this approach, two identical amino acid esters are introduced onto the monophosphate moiety through a P−N bond in order to mask the negative charges.…”
Section: Introductionmentioning
confidence: 99%